Allah’ın Varlığı’nı Aklen Bilmeye İlişkin Mâtürîdî’nin Fıtrat Delili / The Argument of “al-Fitrah” to Prove The Existence of God Accordingto al-Maturidi - aygün, fatma (Journal of History Culture and Art Research, 2015)
The Argument of “al-Fitrah” to Prove The Existence of God Accordingto al-Maturidi Abstract Al-Maturidi is one of the foremost and most important thinkers in the history of Islamic thought. So that Al-Maturidi (333/944) is the most powerful figure in Abu Khanife School and has the biggest share in the establishment of Followers of Sunnah kalam. The aim of this study is to interpret the concept of "al-fitrah", "fitratallah" (nature) and to investigate the possibility of rational knowing the existence of God with an intrinsic element of human (al-fitrah) according to the thinking of Al-Maturidi. The whole characteristics of all creatures, especially human being, brought by the genesis called “nature”(al-fitrah). The concept of al-fitrah contains all of beings in the world; accordingly, al-fitrah symbolizes creation of human. Humans are endowed with many biological, mental and spiritual abilities by born, not a result of work. Man also has innate moral-religious abilities that one of them is “nature/fitrah”. As a common agreement among psychologists and psychologists of religion, human is a believer as well as a thinker. This feature of believing comes from his nature. In the same way, Al-Maturidi believed that human have some dispositions from the birth. According to Al-Maturidi, creation is the consciousness of existence and uniqueness of God that is temperamental in all human beings. This feature of believing is inherent but the framework of this ability has not been determined yet. According to Al-Maturidi, God provides human a several inner qualities such as reason/aql, senses and feelings. These inner supports are actually facilities for human. With reference to the idea that the human is a cognizant (rational) creature, Al-Maturidi argues that he has reasonable and fair reasons for believing in a Creator; and he also uses the evidences such as “disposition" (skills coming with creation) that he links with the term nature (Khilkah). Talkingabout the fitrah of human is talking to the meaning and purpose the existence of human. Meaningfulness and purposefulness is the first law of the creation. Nature and dispositions, skills of human would indicate that there is a meaning and purpose, and hence points to the existence of God. In short, this article explores arguments of Maturidi regarding his opinions on knowing the existence of God by the fitrat/nature. Allah’ın Varlığı’nı Aklen Bilmeye İlişkin Mâtürîdî’nin Fıtrat Delili (Hilkât Delili) Öz İslâm düşünce tarihinde yer alan etkili düşünürlerden biri de Mâtürîdî’dir. Öyle ki Mâtürîdî (333/944), Ebû Hanîfe geleneğinin en güçlü simasıdır ve Ehl-i Sünnet kelâmının kuruluşunda en büyük paya sahiptir. Bu çalışmanın amacı ise Mâtürîdî’nin düşünce dünyasında göze çarpan fıtrat ve fıtratullah kavramlarını açıklamak ve insanın kendisine ait aslî bir özelliği yani fıtrat ile Allah’ın varlığını aklen bilmenin imkânını araştırmaktır. Başta insan olmak üzere, tüm varlıkların yaratılıştan sahip oldukları özelliklerin tamamına “fıtrat” denmektedir. Fıtrat insanın yaratılış biçimini sembolize etmektedir, dünyadaki bütün canlılar fıtrî denilen bir yapıya göre yaratılmıştır. İnsan birçok biyolojik, aklî, ruhî donanım ve yeteneklere doğuştan sahip olduğu, onları sonradan kazanmadığı bilinir. Yani insanın doğuştan sahip olduğu ahlakî-dinî yetenekleri bulunmaktadır ki bunlardan biri de “fıtrat”tır. Psikolog ve din psikologlarının ortak kabulüne göre insan düşünen varlık olduğu kadar inanan da bir varlıktır; onda inanma özelliği yaratılış yani verili olan yapısal donanım/kâbiliyet gereğidir. İşte Mâtürîdî doğuştan getirilen yeti ve yeteneklerin varlığını kabul etmiş, Allah’ın insanı akıl, duyu ve duygular gibi gelişmeye müsait bir takım içsel özelliklerle donatarak yarattığını savunmuştur. Bu iç destekler aslında insana tanınan imkânlar şeklinde anlaşılabilir. Mâtürîdî, insanın bilen (rasyonel) bir varlık oluşundan hareketle Yaratıcı’nın varlığına inanmasının haklı ve mâkul sebeplere dayandığını belirtmiş, hilkât terimiyle ilişkilendirdiği "fıtrat" (yaratılıştan doğruyu bulmaya elverişli kâbiliyetler) delilini kullanmıştır. Esasen insanın fıtratından bahsetmek, insanın varlığının anlam ve amacından söz etmektir, anlamlılık ve amaçlılık yaratılışın ilk yasası değerindedir. İnsanın doğası, eğilimleri, kâbiliyetleri anlam ve amacın varlığına ve dolayısıyla Allah’ın varlığına işaret etmektedir. İşte bu makalede fıtrat delilini kullanan Mâtürîdî’nin Allah’ın varlığını bilmeye yönelik ortaya koymuş olduğu argümanlar ele alınmış ve tartışılmıştır.